1965
DOI: 10.1177/004051756503500604
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observations on Cellulose Graft Copolymers: Radiation Induced Rayon-Styrene Graft Copolymers1

Abstract: Three types of commercial rayon (Fortisan, high-tenacity tire yarn, and modifiertype, high wet modulus yarn) were grafted with styrene, using the direct radiation method with gamma-rays from Co-60. The grafted filaments were examined in the electron microscope to investigate their morphology and fine structure, the location and distribution of polystyrene in the fiber, and whether the polystyrene was truly grafted.In all three grafted fibers, the polystyrene was distributed throughout the cross section of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1966
1966
1975
1975

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Caro (84) concisely outlined the methods, problems and procedures of autoradiography in EM. After an evaluation of the quantitative aspects in terms of resolution, sensitivity, and specimen radioactivity, Salpeter and Bachman (517) estimated that the resolution of an individual silver deposit as recorded on an electron micrograph may soon be in the range of 300 A. The use of S35 in EM was demonstrated by Fewer et al (156).…”
Section: Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Caro (84) concisely outlined the methods, problems and procedures of autoradiography in EM. After an evaluation of the quantitative aspects in terms of resolution, sensitivity, and specimen radioactivity, Salpeter and Bachman (517) estimated that the resolution of an individual silver deposit as recorded on an electron micrograph may soon be in the range of 300 A. The use of S35 in EM was demonstrated by Fewer et al (156).…”
Section: Biologymentioning
confidence: 99%
“…They are similar to the fibers of the mitotic spindle and in certain cells some of the tubules are connected with satellites of the centrioles. In a study of the fine structure of microtubules of nucleated red blood cells by negative staining, Gall (182) observed that the individual microtubules were 300 A. in diameter and of various lengths, up to tens of microns. The wall consisted of 12 to 14 longitudinal subunits arranged in a circular pattern, an observation consistent with those of Ledbetter and Porter (349) who reported 13 subunits in transverse sections.…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopical observations of radiation-induced rayon-styrene graft8 copolymers were published by Kaeppner and Huang in 1965. 4 The present paper reports electron microscopical investigations into both the relationship of the structure of the vinyl-cotton graft polymer to the original morphology of the cotton fiber and the distribution of the grafted vinyl polymer in the cotton fiber structure. The grafted vinyl monomers investigated in this study were acrylonitrile styrene, methyl methacrylate, and vinyl acetate.…”
mentioning
confidence: 99%
“…action of styrene, acrylonitrile, methyl methacrylate, and other vinyl monomers with cellulosic films, filter paper, cellulose esters, cotton, and regenerated cellulosic fibers have been published. [2][3][4] Work in this area by Arthur and his co-workers a t the Southern Utilization Research and Development Division has been concerned with preparing radiation-induced graft copolymers of cotton and various vinyl monomers while retaining the fibrous nature and high molecular weight of the cotton c e l l~l o s e .~-~~ The copolymer technique results in enhancement of the best properties of cotton and acquisition of the properties of the grafted vinyl polymer and therefore more useful, new cotton products for specific end uses. These workers have found that the radiation-induced grafting of vinyl monomers to cotton leads to increased elongation, toughness, abrasion resistance, thermoplasticity, and rot resistance, and decreased stiffness and permanent set.…”
mentioning
confidence: 99%